Guide to the Architecture of Minnesota - Gebhard, David (Book collections on Project MUSE., 1974)
Traces Minnesota?s architectural development in eight regions of the state from territorial days to the present and outlines tours of the state?s landmarks. A perfect companion for sight-seeing trips.